PENGETAHUAN ORANG MUNA TENTANG SUMBER AIR BERSIH DARI PEPOHONAN - Ruslin Ruslin; Wa Ode Sifatu; Ashmarita Ashmartia (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This study aims to determine the knowledge and methods of extracting clean water from trees in Munanese in Wuna Village, District of Tongkonu, Muna Regency. This study uses a qualitative method with data collection techniques through observation and in-depth interviews. The results of this study indicate that since ancient times Munanese has had local knowledge about the process of extracting clean water from trees called "dee tinda", already carried out by the Munanese to overcome the shortage of clean water, especially in the dry season. The process of getting clean water from trees in Munanese, first injuring tree trunks and then tied using reeds. At the ends of the reeds are inserted into jerry cans. This method was carried out because this Wuna village is one of the villages that has a rocky topography, surrounded by mountains and has a barren red soil structure resembling sand. So, in this village water sources are very difficult to find. This knowledge has been passed on to children in the Wuna Village community for generations. Keywords: local knowledge, clean water, trees, Munanese